JEP 2020
DOI: 10.7176/jep/11-27-17
|View full text |Cite
|
Sign up to set email alerts
|

Combating the impact of COVID- 19 on Public University Students through Subsidized Online Class: Evidence from Bangladesh

Abstract: We strived to explore the impact of COVID-19 pandemic on public university students with barriers to the online class through surveyed 1092 students of 15 public universities in Bangladesh using Google Form. Eight barriers were explored. About half, 542(49.6%) students shouldered learning-related costs, 489(45%) students had part time job, 461(42.2%) had COVID-19 patients nearby, 805(73.7%) faced income reduction, 367(75.2%) lost parttime jobs and 688 (63%) had financial crises, 703(64.3%) deterioration of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Bangladesh Bureau of Statistics reported that 62% of the households in Bangladesh do not have stable internet at home, and only 8.7% of the poorest households have internet ( 34 ). Besides, near 50% of students from various public universities in Bangladesh failed to bear internet charges during the COVID-19 crisis ( 35 ). The aforementioned reasons could clarify why about 52.1% of our participants were away from appropriate e-Learning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Bangladesh Bureau of Statistics reported that 62% of the households in Bangladesh do not have stable internet at home, and only 8.7% of the poorest households have internet ( 34 ). Besides, near 50% of students from various public universities in Bangladesh failed to bear internet charges during the COVID-19 crisis ( 35 ). The aforementioned reasons could clarify why about 52.1% of our participants were away from appropriate e-Learning.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, along with the reduction in active study hours, a general decrease in attendance has also been observed by an earlier study as the overall attendance in online classes reached as low as 40% ( 36 ). Another investigation reported a significant decrease in study time by more than 2 h amid the COVID-19 lockdown ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations